Equality via bottom-up referendums? The role of initiators - Geißel, Brigitte; Krämling, Anna (Frontiers in Political Science, 2024)
Direct democratic instruments are discussed by politicians and academia as a means to bring citizens “back in” and thereby to increase support for democracy. Especially bottom-up referenda are expected to offer disadvantaged groups an opportunity to put their issues on the agenda. Yet, the question remains open whether they are really successful in this regard. Are disadvantaged groups able to pursue their interests via direct democratic instruments? Or are (successful) bottom-up referenda mostly initiated by groups that are already influential to further improve their status? Encompassing, comparative research is missing. In order to close these research gaps, this paper addresses the following questions empirically: (1) Which groups initiate bottom-up votes? (2) How do the bills proposed by different groups relate to equality? And finally, (3) which bills succeed at the ballot? To answer these questions, we employ a descriptive analysis of all national direct democratic votes in European democracies between 1990 and 2015. We detect that bottom-up direct democratic instruments can give disadvantaged groups an opportunity to put their issues on the agenda. Our findings can serve as a basis for further, in-depth statistical analyses.